2021
DOI: 10.3390/nu13051470
|View full text |Cite
|
Sign up to set email alerts
|

Update on Calcium and Phosphorus Requirements of Preterm Infants and Recommendations for Enteral Mineral Intake

Abstract: Background: With current Ca and P recommendations for enteral nutrition, preterm infants, especially VLBW, fail to achieve a bone mineral content (BMC) equivalent to term infants. During the first 3 years, most notably in light at term equivalent age (<−2 Z score) VLBW infants’ BMC does not catch up. In adults born preterm with VLBW or SGA, lower adult bone mass, lower peak bone mass, and higher frequency of osteopenia/osteoporosis have been found, implying an increased risk for future bone fractures. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 59 publications
0
25
0
12
Order By: Relevance
“…Die Gewichtsentwicklung eines Frühgeborenen bis zu einem postmenstruellen Alter von 34 SSW beträgt etwa 17 g/kg/d (15–20 g/kg/d). Außerdem wird angenommen, dass der Fetus im Rahmen seiner intrauterinen Entwicklung pro Gramm Gewichtszunahme 0,21 mmol Kalzium und 0,15 mmol Phosphat einlagert 1 23 . Hieraus ergibt sich ein Bedarf von ca.…”
Section: Substitutionsprinzipien Zur Präventionunclassified
See 3 more Smart Citations
“…Die Gewichtsentwicklung eines Frühgeborenen bis zu einem postmenstruellen Alter von 34 SSW beträgt etwa 17 g/kg/d (15–20 g/kg/d). Außerdem wird angenommen, dass der Fetus im Rahmen seiner intrauterinen Entwicklung pro Gramm Gewichtszunahme 0,21 mmol Kalzium und 0,15 mmol Phosphat einlagert 1 23 . Hieraus ergibt sich ein Bedarf von ca.…”
Section: Substitutionsprinzipien Zur Präventionunclassified
“…Während etwa 98 % des aufgenommenen Kalziums zur Knochenmineralisation dient, werden hierzu nur etwa 80 % des Phosphats verwendet. Das molare Ca/Pho-Verhältnis zur Knochenaggregation beträgt näherungsweise 1,67:1, das molare Gesamtverhältnis im Körper beläuft sich auf 1,36:1 1 .…”
Section: Substitutionsprinzipien Zur Präventionunclassified
See 2 more Smart Citations
“…An imbalance between bone formation and bone resorption, favoring bone removal, was observed. Mihatsch et al [12] reviewed the physiology of fetal mineral accretion and preterm infants' mineral absorption, and concluded that calcium and phosphorus requirements depend on weight gain. They additionally concluded that current calcium and phosphorus recommendations systematically underestimate the needs of preterm infants, given a target neonatal weight gain above 17 g/kg/day, particularly for Ca; therefore, a higher enteral fortifier/formula mineral content, or individual supplementation, is required.…”
mentioning
confidence: 99%